DAMPAK MEDIA GAMBAR DALAM PEMBELAJARAN MENULIS PUISI OLEH SISWA KELAS IV SD NEGERI 29 BANDA ACEH - Bukhari Bukhari; M. Yamin; Fauzi Fauzi (Universitas Syiah Kuala, 2021)
Teaching media is an important aspect in teaching at elementary school. Poetry writingskill of students is still below standard which is 75. Teaching activity is still based onstudent’s imagination in creating poetry, this results in the students’ poetry are notproductive. Besides, many teachers do not make use of environment or picture-media as thesource of inspiration in poetry writing. This research wanted to know the influence of usingpicture-media in teaching writing poetry at grade four elementary school 29 Banda Aceh.The approach used in this research is quantitative. The population is the students ofelementary school 29 Banda Aceh which consist of 52 students. The samples are 52 studentswhich consisted of 26 students from grade IV A and 26 students from grade IV B. Data wascollected using test and was analyzed using t-test. The result shows that there is asignificant difference between experiment class (IVA) and control class (IVB). The result ofresearch supports the hypothesis that using picture media in poetry writing skill influenceelementary school students grade four at elementary school 29 Banda Aceh. It is proved byt-count = 5,54 while t-table = 2,00. Therefore, the alternative hypothesis (Ha) saying thatthere is an influence of poetry writing skill toward student taught by using picture-media atelementary school 29 Banda Aceh is accepted.